The effect of broadband internet on establishments' employment growth: evidence from Germany - Stockinger, Bastian (Nürnberg, 2017)
"This study investigates the effects of local broadband internet availability on establishment- level employment growth. The analysis uses data for Germany in the years 2005-2009, when broadband was introduced in rural regions of Western Germany and in large parts of Eastern Germany. Technical frictions in broadband rollout are exploited to obtain exogenous variation in local broadband availability. The results suggest that broadband expansion had a positive effect on employment growth in the Western German service sector and a negative effect in Western German manufacturing. This pattern of results is driven by pronounced positive effects in knowledge- and computer-intensive industries, suggesting that it is the actual use of broadband in the production process that leads to complementary hiring, respectively a slowdown of employment growth, in the respective sectors. For Eastern Germany, no significant employment growth effects are found." (Author's abstract, IAB-Doku) ((en))